Enabling a Comprehensive Teaching Strategy: Video Lectures - Brecht, H. David; Ogilby, Suzanne M (Journal of information technology education, 2008)
This study empirically tests the feasibility and effectiveness of video lectures as a form of video instruction that enables a comprehensive teaching strategy used throughout a traditional classroom course. It examines student use patterns and the videos' effects on student learning, using qualitative and nonparametric statistical analyses of survey responses and student grades. Groups of student course grades are compared with and without video lectures available. Video lectures are CD and web viewable files that present lecture materials and narrative instruction from a course's instructor. They are used as additions to classroom lectures and are not recordings of classroom lectures. In these lectures, the instructor uses Microsoft Office content files, narrative instruction, and screen writing with the keyboard and mouse pointer to deliver the lecture. Video lectures serve major strategic purposes. First, they give additional teaching time to students who cannot fully understand the course material through the classroom lectures and support materials such as the textbook. Students can view and study the instructor's lectures as often as they wish until they understand material. This study resource is particularly important in teaching a broad spectrum of students. Second, video lectures allow classroom coverage of more complex and challenging subject material that is more interesting to many students. Students who are overwhelmed by these information-packed classroom lectures have the video lectures to study, which cover both the basics and the more advanced material. Moreover, some of the time freed in classroom lectures can be converted to problem-solving lab days that focus on active learning. On these lab days, students are given complex and topic-comprehensive problems to solve. These problems aggressively challenge and move forward students' understanding and skill in working with the course material. Because video lectures are available as a support teaching resource, the labs can be used to involve students in solving problems that integrate multiple threads of a topic. Survey results indicate that many students accept and use video lectures as contemplated by this teaching strategy. The extent to which students use the videos is expected to be associated with more than the need for additional teaching time since alternative study resources are always available. Video use frequency and patterns are expected to be at least in part related to each student's learning style preferences. The paper identifies some types of learning style preferences to which video lectures appeal. A statistically significant 68.5% of students using the videos said they helped understand course information and prepare for midterm exams. A statistically significant 72.2% said the videos helped do homework and prepare for weekly exams. Moreover, a statistically significant 63% of students said they provide tutoring help. These use patterns indicate broad acceptance of the computer-based instruction in video lectures, delivered by the course instructor, as a supplementary resource in a traditional course. They indicate that video lectures appeal to many students for a variety of purposes, and are effective for learning. Regarding course grades, survey responses indicate that the video lectures helped 20.4% of students pass the course. Observing grade data, 24.2% of students without the videos failed the course. This rate dropped to 6.8% for the sample group with the videos available--a substantial improvement. Evaluating video lectures as a study resource for comprehensive final exams, they provide an entire semester's lectures delivered by the instructor. Final exam data show that the availability of video lectures improves final exam grades for all grade ranges. (Contains 3 figures.)